If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2e + 3 = 0 Reorder the terms: 3 + 2e = 0 Solving 3 + 2e = 0 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2e = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2e = 0 + -3 2e = 0 + -3 Combine like terms: 0 + -3 = -3 2e = -3 Divide each side by '2'. e = -1.5 Simplifying e = -1.5
| 4(4x+7)-19=100 | | 5(10-3b)=105-5b+4(11b-4b) | | 5=z-2 | | 5(10-3b)=150-8b+4(11-4b) | | -17=13+6k | | 5(4x+3)=9(x-2) | | 9(x+3)+3(x+3)=5x-5 | | 16=-7-8+3x | | 5y+10y=4y-10 | | 3x+7=-2x-3 | | 9z-24=3z | | 7/3.10n/7n | | .055x+5.767=.04x+5.761 | | x+2.4=2+1.7 | | 1100=n+20 | | x^3-h^3=0 | | 5-(x+9)=3+(x-12) | | (49x-36)+27=40 | | y=5(-10)+7 | | 7d-6=9 | | .5x+.26(300)=.25(156) | | 12-4v=45 | | 7d+3=20 | | 5/2y-7=3/y | | 0.45s=9.25 | | .05x+.26(300)=.25(156) | | 24-6r=24-r | | .05x+.24(300)=.25(156) | | s=0.45+9.25 | | 5-3/4x=7/12 | | -18=-3u | | 3x-4-2x+10=6x-2x+10 |